UPAYA MEWUJUDKAN KEBIJAKAN RAMAH DISABILITAS DALAM PELAKSANAAN PROGRAM VAKSINASI COVID-19 - Pawi, Andi Anugrah; Susetyo, Heru (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2022)
The Corona Virus Disease 2019 (Covid-19) pandemic causes Severe Acute Respiratory Syndrome and in some cases even causes Acute Respiratory Distress Syndrome caused by the Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2). In Indonesia, the death rate from Covid-19 in February 2021 was the highest in Asia and was ranked 17th in the world. Meanwhile, Indonesia's Case Fatality Rate (CFR) is quite high, at 2.8%, surpassing the global CFR (2.3%). The Government of Indonesia has responded to the virus with various policies that focus on three things, namely education, treatment, and law enforcement. Currently, the policy issued by the government is the National Vaccination Program. This policy also applies to persons with disabilities. It is known, in several fields of life, it is not uncommon for people with disabilities to become victims of discrimination. The same is true in the world of health, especially with regard to the Covid-19 vaccination service. On that basis, this article analyzes the implementation of national programs in dealing with Covid-19 for disabled people based on international instruments and national laws. The results show that the implementation of the Covid-19 vaccination program in Indonesia has been carried out by taking into account the special needs of vulnerable groups, including people with disabilities.